The Blindness of Europe: New Fabrications in the European Educational Space - Nóvoa, António (2013)
After a slow start during the 70s and 80s, education took on a new importance after the adoption of the Maastricht Treaty in 1992. From that date onwards, numerous texts and documents would gradually build a «European educational space». The Lisbon Strategy of 2000 is an important milestone in this process. The main reference point of the 21st century is the Education & Training 2010 Work Program, which sets a clear framework at the European level for education and training. Recently, there was a new turning point of great significance, with the approval of Europe 2020 and especially with the launching of the Rethinking Education strategy. We are facing continuities and changes that need to be analyzed carefully. That is what I intend to do in this article entitled «The Blindness of Europe: New Fabrications in the European Educational Space». In the first section, I will recall the major turning points in educational policies in the last two decades. In the second section, the analysis will focus on the new Education and Training 2020 (ET 2020) program and the Rethinking Education strategy launched in November of 2012. The final considerations seek to promote a broader reflection on the new fabrications that are taking place in the European educational space: i) Is Europe a solution or a problem?; ii) What education for what Europe? iii) How to study educational policies in Europe?